Dana BOSP sebagai Instrumen Pemberdayaan Literasi Kewargaan di Pendidikan Nonformal (Studi Kasus di PKBM Provinsi Jawa Timur) - Adea, Adea; Syukran, Syukran; Darmison, Vivi Resti; Arni, Herda; Ansori, Aan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Community Learning Centers (PKBM) in East Java play a crucial role in expanding access to non-formal education and fostering civic engagement. However, the implementation of the Operational Assistance for Education Units (BOSP) faces persistent challenges, including limited tutor capacity, low community participation, and insufficient financial transparency. This study aims to analyze how BOSP funds can be optimized to strengthen civic literacy in PKBM. Using a descriptive qualitative approach, data were collected through interviews, participatory observations, and document analysis in four PKBM located in Malang, Sidoarjo, Banyuwangi, and Jember. The findings reveal that BOSP funds have been effectively utilized for tutor training, development of contextual learning materials, and participatory activities such as village democracy training and election simulations. These initiatives have enhanced learners’ civic awareness and social participation. In addition, transparent financial practices such as public reporting and open forums have increased institutional accountability and community trust. Nevertheless, delays in fund disbursement and managerial limitations remain as key obstacles. Strengthening collaboration between government, PKBM, and local communities is recommended to ensure that BOSP becomes a sustainable instrument for inclusive and participatory civic education.